A novel quinternary alloy (Cu2Zn1−xCdxSnS4) nanostructured sensor for biomedical diagnosis. (19th August 2016) - Ibraheam, A S; Al-Douri, Y; Gopinath, S C B; Hashim, U
Abstract: A new quinternary alloy (Cu2 Zn1−x Cdx SnS4 ) nanostructure with different proportions of cadmium (Cd) was synthesised using spin coating technique on oxidized silicon (100) substrate and analysed by x-ray diffraction (XRD) and photoluminescence (PL). The XRD peaks were shifted towards the lower angle side with increasing Cd concentrations. A shift of PL band gap from 1.79 eV (x = 0) to 1.69 eV (x = 1) was observed. We attributed this phenomenon to the phase transition from kesterite to stannite phase in the series of Cu2 Zn1−x Cdx SnS4 (0 ≤ x ≤ 1) quinternary alloy nanostructures. Further, the generated novel structure was found to be more suitable for biomedical diagnosis, as evidenced by dengue serotype-2 detection with higher specificity. The biosensor shown with quinternary alloy nanostructure could attain the sensitivity to 100 fM and able to discriminate specific DNA from dengue against single and triple mis-match sequences. The biosensor demonstrated here with a novel Cu2 Zn1−x Cdx SnS4 quinternary alloy nanostructure opens the way for developing high-performance biosensors.